(untitled) (Studia austriaca, 2020)
Gregor von Rezzori’s novel Der Schwan presents a highly symbolic narrative structured on important dichotomies such as life and death, beginning and end, childhood and adulthood. The young narrator experiences different situations, such as the suicide of his uncle, the unwished-for separation from his beloved sister, his first encounter with a girl, and the murder of a swan, to all of which he reacts in a passive way. However, he remains entangled in his family bonds and all these experiences come to symbolize the predestined nature of his life, which is and will be characterized by a series of failures and by his decline.